COVID-19 anxiety and organizational commitment among front-line nurses: Perceived role of nurse managers' caring behavior - Manar Ahmed Elbadawy Abdelrehem Faramawy; Aziza Ibrahim Abd El Kader (Tehran University of Medical Sciences, 2021)
Background & Aim: Anxiety related to the COVID-19 is prevalent amongst the nursing workforce potentially affecting nurses' well-being and their organizational commitment. The nurse manager's caring behavior has been recognized as a crucial indicator of nurses' resilience with the COVID-19 pandemic. This study aimed to investigate the effect of COVID-19 anxiety on frontline nurses' organizational commitment and their perception of nurse managers' caring behavior. Methods & Materials: This study utilized an explanatory research design; hence, a convenient sample consisted of 60 registered nurses working at three selected medical intensive care units located in one of the Cairo University Teaching hospitals, Egypt was selected. Data were collected using the Coronavirus Anxiety Scale, Nursing Staff Organizational Commitment Questionnaire, and Nurse Managers' Caring Behavior Questionnaire. Statistical Package for the Social Sciences (SPSS) version 20 was used for the data analysis where the descriptive statistics, Simple Linear, and Stepwise multiple regression analysis were applied. Results: The highest-rated anxiety problem of COVID-19 was appetite loss (x ̅=3.03, SD = ±0.88). Human respect as one of the perceived nurse managers caring behaviors emerged as a strong predictor (Partial R2 = 0.104, p= .017) in increasing the frontline nurses' organizational commitment, while COVID-19 anxiety has a significant decreasing effect (Partial R2 = 0.435, p<0.001) on it. Conclusion: COVID-19 anxiety has affected the frontline nurses' organizational commitment and their perceived nurse managers' caring behavior. COVID-19 anxiety should be addressed and rectified by providing appropriate managerial caring behavior and support to boost nurses 'organizational commitment.